An overview of the non-canonical inflammasome. (December 2020) - Downs, Kevin P.; Nguyen, Huyen; Dorfleutner, Andrea; Stehlik, Christian
Abstract: Inflammasomes are large cytosolic multiprotein complexes assembled in response to infection and cellular stress, and are crucial for the activation of inflammatory caspases and the subsequent processing and release of pro-inflammatory mediators. While caspase-1 is activated within the canonical inflammasome, the related caspase-4 (also known as caspase-11 in mice) and caspase-5 are activated within the non-canonical inflammasome upon sensing of cytosolic lipopolysaccharide (LPS) from Gram-negative bacteria. However, the consequences of canonical and non-canonical inflammasome activation are similar. Caspase-1 promotes the processing and release of the pro-inflammatory cytokines interleukin (IL)-1β and IL-18 and the release of danger signals, as well as a lytic form of cell death called pyroptosis, whereas caspase-4, caspase-5 and caspase-11 directly promote pyroptosis through cleavage of the pore-forming protein gasdermin D (GSDMD), and trigger a secondary activation of the canonical NLRP3 inflammasome for cytokine release. Since the presence of the non-canonical inflammasome activator LPS leads to endotoxemia and sepsis, non-canonical inflammasome activation and regulation has important clinical ramifications. Here we discuss the mechanism of non-canonical inflammasome activation, mechanisms regulating its activity and its contribution to health and disease.